PELATIHAN DESIGN THINKING DAN PROTOTYPING UI/UX UNTUK IDE STARTUP SISWA SMA - Syamsul Rijal; Aulia Rahmawati; Rezty Amalia Aras; Furqan Zakiyabarsi; Hany Alexandria; Muhammad Fachrul Salam; Yogi Hady Afrizal; Andi Jamiati Paramita; Andi Hutami Endang; Kiki Resky Ramdhani Sucipto; Widia Febriyani (Nusantara Hasana Journal, 2026)
The development of digital technology has created a new ecosystem that requires young people, particularly Generation Z, to become not only passive digital consumers but also creators of innovative solutions through the startup ecosystem. An empathy-based Design Thinking approach is considered effective in producing human-centered solutions while shaping resilient, solution-oriented young entrepreneurial character. However, students at SMA SPIDI Maros still faced difficulties in understanding business idea validation and UI/UX prototype design. This community service program aimed to provide Design Thinking and UI/UX Prototyping training to support students' startup idea development while enhancing their digital literacy. The method employed a two-session training and workshop, consisting of a Design Thinking presentation and a UI/UX Prototyping workshop using Figma, implemented through four stages: identifying participant needs, designing materials, conducting the activity, and evaluation with follow-up. The program was held on 28 January 2026 and attended by 32 participants from grades 10 to 12. Evaluation results showed all indicators fell into the "Very Good" category, with the overall usefulness indicator scoring highest at 4.84/5 (97% agreement), while ease of using Figma scored lowest at 4.41/5 due to limited workshop time. These findings underscore the importance of continuous, multi-session mentoring programs for high school students in the future.